Design and implementation of a PV-tied effective inverter with high reliability and low THD for distribution-grid applications - Nyamathulla, Shaik; C., Dhanamjayulu (Frontiers in Energy Research, 2024)
Researchers have focused on multilevel inverters (MLIs) due to their use in electric vehicles, renewable energy systems, and industrial applications. This paper proposes a new design for a single-phase 21-level asymmetrical MLI for photovoltaic (PV) applications that reduces the number of components, voltage stress, overall size and cost. An enhanced incremental maximum power point tracking (EINC-MPPT) is used in the PV standalone system to offer a fast dynamic response, track maximum power and regulate the PV module output voltage. This paper presents the PV boost DC-DC single-input multi-output (SIMO) converter linked to the solar panels to provide the supply voltages for the inverter. A level-shifted constant multicarrier sinusoidal pulse width modulation (LSCMSPWM) technique is used to produce the better-synthesized output waveform from the MLI, resulting in low total harmonic distortion (THD) also meeting IEEE standards. The suggested MLI is simulated in MATLAB/Simulink and tested with a hardware prototype under various load conditions. The proposed MLI is suitable for medium-power and grid-connected renewable energy systems applications. The qualitative and quantitative parameters of the proposed MLI have been evaluated using parameters such as cost function (CF), number of components, reliability, THD, total standing voltage (TSV) and these parameters are compared with the existing MLIs.